2004
DOI: 10.1007/bf03192505
|View full text |Cite
|
Sign up to set email alerts
|

Ranging patterns of two syntopic gerbillid rodents: a radiotelemetry and live-trapping study in semi-desert habitat of Kalmykia, Russia

Abstract: 2004. Ranging patterns of two syntopic gerbillid rodents: a radiotelemetry and live-trapping study in semi-desert habitat of Kalmykia, Russia. Acta Theriologica 49: 17-31.We studied ranging patterns of syntopic folivorous and granivorous gerbils (Meriones tamariscinus Pallas, 1773 and Meriones meridianus Pallas, 1773, respectively) by means of radiotracking and live-trapping in Kalmykia, southern Russia. We hypothesized that ranging patterns exhibited by these rodents would differ in accordance with difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We previously have shown that sociability is a consistent personality trait in M. meridianus (Tchabovsky et al 2019b, 2024), which, according to this study, seems unrelated to the colonization process. We attribute this to the overall low sociability as a species-specific trait of this socially indifferent gerbil (Gol’tsman et al 1994; Tchabovsky et al 2004; Shilova, Tchabovsky 2009). In particular, midday gerbils showed no preferences between familiar and unfamiliar conspecifics in the preference tests (Tchabovsky et al 2019b), suggesting that their response to social novelty in colonies may be weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously have shown that sociability is a consistent personality trait in M. meridianus (Tchabovsky et al 2019b, 2024), which, according to this study, seems unrelated to the colonization process. We attribute this to the overall low sociability as a species-specific trait of this socially indifferent gerbil (Gol’tsman et al 1994; Tchabovsky et al 2004; Shilova, Tchabovsky 2009). In particular, midday gerbils showed no preferences between familiar and unfamiliar conspecifics in the preference tests (Tchabovsky et al 2019b), suggesting that their response to social novelty in colonies may be weak.…”
Section: Discussionmentioning
confidence: 99%
“…Meriones meridianus is a small (50-60 g of adult body mass), short-lived (ca eight months of life expectancy) nocturnal-diurnal mainly granivorous psammophilous gerbil inhabiting deserts and semi-deserts of Central Asia, Northern China, and Southern Russia (Wang et al 2013; Nanova et al 2014; Tchabovsky et al 2019a; Yang et al 2020). Midday gerbils live solitarily or in loose aggregations: males and females are not territorial, do not form pair bonds, are socially promiscuous, interact rarely, display little agonistic or amicable behaviour, and, on the whole, are socially indifferent (Gol’tsman et al 1994; Tchabovsky et al 2004; Shilova, Tchabovsky 2009; Tchabovsky et al 2019b). Breeding season in Kalmykia typically lasts from early April to mid-September.…”
Section: Methodsmentioning
confidence: 99%